Taxpayer Compliance Based on Awareness and Policy - Suhendar, Dadang; Hakim, Dani Rahman (Accounting Analysis Journal, 2021)
This study examines the effect of tax policy aspects and awareness on taxpayer compliance in Kuningan Regency. The policy aspects in this study have manifested by tax sanction and Fiscus service quality. This study uses questionnaires which have distributed by random sampling technic. By using the multiple linear regression analysis, this study reveals that tax sanctions, Fiscus service quality, and taxpayer awareness positively affect taxpayer compliance. Aspects of government policy in tax sanctions are more significant than taxpayers' awareness to affect taxpayer compliance. It means that strict tax sanctions have been necessary accompanied by improving the Fiscus services quality as part of the tax services paradigm. This study can be used as a reference to reexamine the determinants of taxpayer compliance, especially in areas with the same characteristics as the object of this study. Future research is expected to examine the equilibrium between economic and non-economic variables more deeply in increasing taxpayer compliance. It is essential because which variable most determines taxpayer compliance is still unclear, whether theoretically or practically. Keywords: Awareness, Compliance, Taxpayers, Fiscus Services Quality